Coercion experience of patients with mental illness in a tertiary care hospital in Kerala - Anagha Unnikrishnan; T K Saleem; C A Smitha (Kerala Journal of Psychiatry, 2023)
Background: Coercion is a negative experience that interferes with the basic freedom and rights of patients with mental illness. The present study focuses on understanding the experience of coercion in patients with mental illness during their admission to a tertiary care hospital. Objectives: The study aims to assess the coercion experience of patients with mental illness who are undergoing treatment from a teaching hospital in a northern district of Kerala. The study also looked into the relationship between coercion experience and socio-demographic variables. Methods: A semi-structured interview schedule to assess socio-demographic variables and MacArthur Admission Experience Survey to assess the coercion experience of patients with mental illness were used in this study. The study sample included 84 patients with mental illness who had admission experience in the last two years. Results: Findings of the study revealed that 36.9% of patients with mental illness experienced high coercion and another 29.8% reported a moderate level of coercion. Affective reactions to hospitalization showed confusion (48.80%) and sadness (40.48%). A significant negative correlation was established between coercion experience and age, drug compliance and age of onset of illness. There was no significant relationship between coercion experience and sex, marital status, religion, socio-economic status, educational status, occupational status, diagnosis category, place of residence and regularity of treatment. Conclusion: A significant proportion of patients report coercive experiences during their admission for psychiatric treatment. Coercion is a negative experience that adversely affects the outcome. The study is attempting to highlight whether there is a need to lessen coercion